Cervical vascular lesions associated with ginecorragia - Vega Rizo Patron, Leoncio (2015)
We have found corresponding hysterectomy specimens performed as an emergency treatment before ginecorragias massive, post produced electro-cauterization or post cervical biopsy, vascular lesions, which we would importnacia in its genesis. We study the morphology of these changes and discuss the patogenesos in the light of current knowledge, associated with geenral fenónemo of vasculitides.